Enhancement in the physico-mechanical functions of seaweed biopolymer film via embedding fillers for plasticulture application—a comparison with conventional biodegradable mulch film - Hasan, Muhammad; Chong, Eunice Wan Ni; Jafarzadeh, Shima; Md. Tahir, Paridah; Gopakumar, Deepu Ambika; Tajarudin, Husnul Azan; Thomas, Sabu; H. P. Shawkataly, Abdul Khalil (MDPI, 2019)
This study aimed to compare the performance of fabricated microbially induced precipitated calcium carbonate– (MB–CaCO3) based red seaweed (Kappaphycus alvarezii) bio-polymer film and commercial calcium carbonate– (C–CaCO3) based red seaweed bio-film with the conventional biodegradable mulch film. To the best of our knowledge, there has been limited research on the application of commercial CaCO3 (C–CaCO3) and microbially induced CaCO3 (MB–CaCO3) as fillers for the preparation of films from seaweed bio-polymer and comparison with biodegradable commercial plasticulture packaging. The results revealed that the mechanical, contact angle, and biodegradability properties of the polymer composite films incorporated with C–CaCO3 and MB–CaCO3 fillers were comparable or even superior than the conventional biodegradable mulch film. The seaweed polymer film incorporated with MB–CaCO3 showed the highest contact angle of 100.94°, whereas conventional biodegradable mulch film showed a contact angle of 90.25°. The enhanced contact angle of MB–CaCO3 resulted in high barrier properties, which is highly desired in the current scenario for plasticulture packaging application. The water vapor permeability of MB–CaCO3 based seaweed films was low (2.05 ± 1.06 g·m/m2·s·Pa) when compared to conventional mulch film (2.68 ± 0.35 g·m/m2·s·Pa), which makes the fabricated film an ideal candidate for plasticulture application. The highest tensile strength (TS) was achieved by seaweed-based film filled with commercial CaCO3 (84.92% higher than conventional mulch film). SEM images of the fractured surfaces of the fabricated films revealed the strong interaction between seaweed and fillers. Furthermore, composite films incorporated with MB–CaCO3 promote brighter film, better water barrier, hydrophobicity, and biodegradability compared to C–CaCO3 based seaweed polymer film and conventional mulch film. From this demonstrated work, it can be concluded that the fabricated MB–CaCO3 based seaweed biopolymer film will be a promising candidate for plasticulture and agricultural application.